Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada Bagian Proyek Divisi Lift Eskalator Servis PT. Jaya Kencana, Jakarta Pusat - Beny Pratama; Pusporini Palupi Jamaludin; Paringsih Paringsih (CV. Aksara Global Akademia, 2025)
This study aims to analyze the effect of work discipline and work motivation on employee performance in the project section of the Lift Escalator Service division of PT. Jaya Kencana, Central Jakarta, both partially and simultaneously. This study uses a quantitative method, with data collection techniques through primary and secondary data. Data analysis includes validity, reliability, normality, multicollinearity, heteroscedasticity, autocorrelation, simple and multiple linear regression tests, as well as t-tests and F-tests. The results of the study indicate that partially, work discipline has a positive and significant effect on employee performance, with a regression equation of Y = 23.998 + 0.409 X1, where the t-count value is 9.019> t-table 1.65263 and a significance value of 0.000 <0.05. Work motivation also has a positive and significant effect on employee performance, with the regression equation Y = 19.944 + 0.437 X2, where the t-count value is 8.450> t-table 1.6526 and a significance value of 0.000 <0.05. Simultaneously, work discipline and work motivation have a positive and significant effect on employee performance, with the regression equation Y = 17.200 + 0.292 X₁ + 0.289 X₂, where the F-count value is 61.283> F-table 3.04 and a significance value of 0.000 <0.05. The correlation coefficient value of 0.620 and the determination coefficient of 38.5% indicate that work discipline and work motivation together explain the variation in employee performance by 38.5%.